2019
DOI: 10.22159/ajpcr.2019.v12i5.31605
|View full text |Cite
|
Sign up to set email alerts
|

Genoprotective Effects of Ethanolic Stem Extracts of Tinospora Cordifolia on Sodium Arsenite-Induced Dna Damage in Swiss Mice Lymphocytes by Comet Assay

Abstract: Objective: The study was aimed to evaluate the DNA protective effects of ethanolic extracts of Tinospora cordifolia stem on Swiss albino mice lymphocytes against the sodium arsenite-induced genotoxicity. Methods: In this experiment, 25 animals of nearly the same age were equally divided. Group 1 (control) fed on tap water while rest four (2, 3, 4, and 5) groups were treated with 4 mg/kg body weight, per orally sodium arsenite for 12 weeks. Sodium arsenite pretreated groups (4 and 5) were followed by admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…A study found that extracts from Guduchi markedly enhanced the rate of cell survival and protected against radiation-induced cytotoxicity and DNA damage in PC12 cells [17]. Another study using ethanolic Guduchi stem extracts reported DNA protective ability on sodium arsenite-induced genotoxicity in lymphocytes from Swiss Albino mice using the comet assay [18].…”
mentioning
confidence: 99%
“…A study found that extracts from Guduchi markedly enhanced the rate of cell survival and protected against radiation-induced cytotoxicity and DNA damage in PC12 cells [17]. Another study using ethanolic Guduchi stem extracts reported DNA protective ability on sodium arsenite-induced genotoxicity in lymphocytes from Swiss Albino mice using the comet assay [18].…”
mentioning
confidence: 99%
“…Our results were also in concordance to the earlier reports where ethanolic extract of T. cordifolia showed reduction in DNA damage in arsenite induced DNA damage in lymphocytes. [ 24 ]…”
Section: Discussionmentioning
confidence: 99%